Improving Multivariate Analysis of Variance (MANOVA) through Advanced Spectral Linear Algebra: A High-Dimensional Data Framework (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Multivariate Analysis of Variance or MANOVA is a very powerful statistical technique for discriminating between several groups in multivariate data sets. With the level of complexity and dimension of newer high-dimensional data sets increasing, under the control of powerful computer technologies, newer spectral-type algebra methods are to be employed if the problem is experiencing exact analytical values with optimizing the efficiency of operation. This current research seeks to unveil a platform by combining MANOVA with higher spectral algebra, hence successful processing of multivariate data. The research problem stems from recognizing that the traditional MANOVA can be insufficient in searching for solutions to high-dimensional and complex data, and hence the necessity to search for more sophisticated methodologies in an attempt to advance analytical efficacy. This current study aims to investigate the effectiveness of the new model in multivariate analysis of data in comparison to the traditional approach. A combined methodology of MANOVA utilizing sophisticated methodology of spectral algebra was the main analytical tool. The main hypothesis supposes that the combination of MANOVA and spectral algebra increases analytical accuracy and efficiency over traditional methods. Early findings indicate that the new model is more efficient as well as accurate and therefore validates the use of MANOVA in the management of multivariate data sets as well as appropriateness in the inclusion of advanced spectral methods in contemporary data analysis of statistics.